2020
DOI: 10.1002/path.5568
|View full text |Cite
|
Sign up to set email alerts
|

SETDB1 promotes gastric carcinogenesis and metastasis via upregulation of CCND1 and MMP9 expression

Abstract: SETDB1 is a histone lysine methyltransferase that has critical roles in cancers. However, its potential role in gastric cancer (GC) remains obscure. Here, we mainly investigate the clinical significance and the possible role of SETDB1 in GC. We find that SETDB1 expression is upregulated in GC tissues and its high‐level expression was a predictor of poor prognosis in patients. Overexpression of SETDB1 promoted cell proliferation and metastasis, while SETDB1 suppression had an opposite effect both in vitro and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 56 publications
2
11
0
Order By: Relevance
“…55 Another study has revealed the association between ccnd1 and setdb1 in gastric cancer, where the upregulation of setdb1 could affect the metastasis via upregulation of ccnd1 and mmp9 . 56…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…55 Another study has revealed the association between ccnd1 and setdb1 in gastric cancer, where the upregulation of setdb1 could affect the metastasis via upregulation of ccnd1 and mmp9 . 56…”
Section: Resultsmentioning
confidence: 99%
“…55 Another study has revealed the association between ccnd1 and setdb1 in gastric cancer, where the upregulation of setdb1 could affect the metastasis via upregulation of ccnd1 and mmp9. 56 Moreover, a few studies have reported the relationship between CCND1 and BRAF, which are the key components of the MAP kinase pathway. CCND1 amplification was associated with BRAF activation mutation in human melanoma.…”
Section: Correlation Of Braf With Other Proteins and Their Associatio...mentioning
confidence: 99%
“…Yu et al found that upregulation of SETDB1 enhanced the transcription of CCND1 and CDK6, thereby promoting proliferation of colorectal cancer cells [ 44 ]. Shang et al observed that high SETDB1 expression may accelerate cell proliferation through the ERG-CCND1/MMP9 axis, which was also associated with adverse prognosis in gastric cancer [ 45 ]. Hence, it has been demonstrated that SETDB1 may regulate the cell cycle genes leading to disease progression in multiple myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…found that the trimethylated state of H3K9 is highly expressed and positively correlated with tumor staging 239,240 . SETDB1 is abnormally overexpressed in GC and plays a crucial role in GC occurrence and metastasis by upregulating β‐catenin and matrix metalloproteinase 9 241,242 . Furthermore, in the xenograft tumor model, the knockout methyltransferase G9a showed a concomitant marked reduction in H3K9 monomethylation and potent inhibition of mechanistic target of rapamycin (mTOR) expression and tumor growth 243 .…”
Section: Abnormal Expression Of Histone‐modifying Enzymes and Human C...mentioning
confidence: 99%